Physician's hesitancy in treating COVID-19 patients and its associated occupational risk factors in Indonesia: an online cross-sectional survey - Dewi Sumaryani Soemarko; Aria Kekalih; Ari Fahrial Syam; Evy Yunihastuti; Herikurniawan Herikurniawan; Mikhael Yosia (Journal of Public Health in Africa, 2023)
This cross-sectional survey aims to investigate physician hesitancy in treating COVID-19 patients in Indonesia, particularly among those who have already contracted the disease, along with associated occupational risk factors. The study involved distributing a questionnaire to physicians across the country, using contact information from the Indonesian Physician Association database. The results show that out of the 383 participants, 25.6% experienced moderate symptoms of COVID-19, and 2.9% required critical care. The study found that 20.3% of physicians demonstrated hesitancy to treat suspected, probable, or confirmed COVID-19 patients. Interestingly, older physicians and those with less experience in treating COVID-19 patients were found to have a higher hesitancy rate, while specialist trainees and those working in public hospitals demonstrated the lowest hesitancy. These findings highlight the significant hesitancy among physicians who have suffered from COVID-19 and underline the need for management and policymakers to take further action to address this issue. Understanding the effects and benefits of physician hesitancy in treating COVID-19 patients is crucial for ensuring the effective delivery of healthcare services during pandemics like COVID-19.